Identification of Floral Resources Used by the Stingless Bee Melipona beecheii for Honey Production in Different Regions of the State of Campeche, Mexico - Román Alberto León-Canul; Juan Bautista Chalé-Dzul; Arely Anayansi Vargas-Díaz; Juan Javier Ortiz-Díaz; Kelly Cristina Durán-Escalante; Eugenio Carrillo-Ávila; Alberto Santillán-Fernández (Diversity, 2023)
The stingless bee Melipona beecheii is experiencing colony decline due to floral resource scarcity caused by deforestation. A study was conducted to identify the floral resources used by M. beecheii using honey samples collected in four regions of the state of Campeche, Mexico. A melissopalynological analysis of sixteen collected honey samples identified 69 plant species from 24 families, and established that Fabaceae was the main plant family visited. Based on botanical origin, seven samples were classified as monofloral and nine as multifloral. The predominant species were Bursera simaruba, Lonchocarpus longistylus, Piscidia piscipula, Senna pallida and Senna racemosa. Shannon diversity index values (2.06–2.55) indicated moderate diversity in floral resources and Simpson diversity index values (0.82–0.89) indicated a moderate dominance of plant species in the studied regions. The results suggest M. beecheii is polylectic with some degree of specialization. The plant species identified as predominant in the studied honey samples are candidates for use in strategies intended to conserve the food resources used by M. beecheii on the Yucatan Peninsula.